Notes on Early Land Plants Today. 38. New combinations and synonyms in Lepidoziaceae (Marchantiophyta) - Cooper, Endymion D.; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Cooper (2013) summarizes the current status of the family Lepidoziaceae and presents a new classification based on recent phylogenetic studies (Cooper et al. 2011, 2012). The classification requires many transfers of taxa and the new combinations and a new synonym are reported here. Ceramanus gen. nov. is newly described and Tricholepidozia comb. et stat. nov. elevated to generic rank. Several of the species require lectotypification, but this is beyond the scope of this nomenclatural note and lectotypes are designated only in two unambiguous cases.